Selection of 3PL providers for overseas market expansion: insights from a Vietnamese company - Nguyen, Thi Minh Hoa; Ménoury, Matéo (Journal of Supply Chain Management Science, 2022)
Logistics outsourcing has become a strategy for companies so that they can focus on their core competency and increase their competitive advantages. Although there has been a wide range of studies on the selection of Third-Party Logistics (3PL) providers during the operation and supply chain management of the companies, research focusing on the phase of market expansion is lacking. The aim of this study is to analyze the selection of 3PL providers with an emphasis on overseas market expansion. A Vietnamese company in the chemical industry aiming to select the most suitable 3PL provider for overseas market expansion to Brazil is considered. The Analytic Hierarchy Process (AHP) is applied to five main criteria that are cost, service, global network, industry experience, and local presence. A list of five 3PL providers is evaluated and ranked. Group decision-making with a sharing approach is used, such that three decision-makers (DMs) achieve a consensus on the assessment. The results indicate that industry experience and responsiveness to urgent occurrences are the two most important criteria when the company chooses a 3PL provider for overseas market expansion, while the lowest priority belongs to communication.